Paul Grice - Chapman, S. author. aut Link
VIII, 247 p.
Keywords: Paul Grice (1913-1988) is best known for his psychological account of meaning, and for his theory of conversational implicature, although these form only part of a large and diverse body of work. This is the first book to consider Grice's work as a whole. Drawing on the range of his published writing, and also on unpublished manuscripts, lectures and notes, Siobhan Chapman discusses the development of Grice's ideas and relates his work to the major events of his intellectual and professional life.